Pengaruh Indeks Harga Saham Syariah Internasional dan Variabel Makroekonomi Terhadap Jakarta Islamic Index (JII) Tahun 2018-2022 - Shovi Wahyuni; Ingra Sovita (CV. ITTC INDONESIA, 2024)
The stock market has a strategic role in the development of a country's economy in the era of globalization, including the Islamic stock market. The Islamic stock market is very important in supporting the economy which can have an impact on real market growth through sharia-based investment. The purpose of this study is to determine the effect of the international sharia stock price index and macroeconomic variables on the Jakarta Islamic index (JII) for the period 2018-2022. This type of research uses quantitative research, namely by estimating regression models using time series data. The data used is secondary data using a sample of 60 consisting of monthly all variables during 2018-2022 which can be from the Closing Price data. This research data analysis technique uses multiple linear regression analysis techniques with the help of the SPSS version 21 program. Based on the discussion that has been stated regarding the Effect of the International Sharia Stock Price Index and Macroeconomic Variables on the Jakarta Islamic Index (JII) for the 2018-2022 period, it can be concluded that the results of this study show that partially the international stock price index variable has a negative and significant effect on the Jakarta Islamic Index (JJI) with a coefficient of 0, the t value is -5,025 < t table 2,003 and a significance value of 0.000 which means less than 0.05. The rupiah exchange rate has a negative and significant effect on the Jakarta Islamic Index (JJI) as indicated by the t value of -7,265 < t table 2.003 and a significance value of 0.000 which is smaller than 0.05, and the inflation rate has a positive and significant effect on the Jakarta Islamic Index (JJI) with a t value of 4,448> t table 2.003 and a significance value of 0.000 which is smaller than 0.05. Simultaneously (f) all variables have a positive and significant effect on the Jakarta Islamic Index (JJI) with a value of f count 43.201> f table 2.764 and a significant level of 0.000, the coefficient of determination shown through the Adjusted R square value of 68.2% while the remaining 31.8% is explained by other factors not included in this study.